Revisiting the window of opportunity for cotranscriptional splicing in budding yeast - Aslanzadeh, Vahid (RNA, 2020)
We reported previously that, in budding yeast, transcription rate affects both the efficiency and fidelity of pre-mRNA splicing, especially of ribosomal protein transcripts. Here, we report that the majority of ribosomal protein transcripts with non-consensus 5′ splice sites are spliced less efficiently when transcription is faster, and more efficiently with slower transcription. These results support the “window of opportunity” model, and we suggest a possible mechanism to explain these findings.